Randomized controlled trial of the Marriage Checkup: Stress outcomes. (16th December 2022) - Leth‐Nissen, Astrid B.; Fentz, Hanne N.; Trillingsgaard, Tea L.; Stadler, Gertraud
Abstract: Several couple interventions targeting relationship distress also show beneficial effects on individual mental health. Yet, strikingly few studies report effects on perceived stress. This study examined the effects of a brief couple intervention, the Marriage Checkup (MC), on perceived stress. We randomly assigned 231 couples to receive two MCs (Weeks 7 and 51) or to a waitlist control. Survey data were collected at seven time points over 2 years and analyzed using multilevel models. We found no significant between‐group treatment effects on average stress at any time point. However, women, but not men, in the intervention group experienced decreased stress after the second MC ( d  = −0.23) and more women in the intervention group (26.5%) compared with the control group (14.9%) experienced reliable improvements in stress after the second MC. Overall, the MC did not result in main effects on stress but caused temporary reliable change in terms of stress relief for women.